Response of ornamental plants to salinity: impact on species-specific growth, visual quality, photosynthetic parameters, and ion uptake - Wang, Zirui; Poudyal, Shital; Kopp, Kelly; Zhang, Yunhua (Frontiers in Plant Science, 2025)
Ornamental horticulture provides substantial economic and environmental benefits, generating billions in annual sales and contributing to urban greening. However, the increasing scarcity of freshwater resources necessitates the use of alternative irrigation sources, such as reclaimed water. Reclaimed water typically contains elevated salt levels that can induce salt stress. Salt stress adversely affects multiple plant traits. Aesthetic quality declines, manifesting as leaf tip burns, discoloration, and necrosis, reducing landscape value and commercial appeal. Growth performance, including biomass production, plant height, and leaf expansion, is limited by osmotic stress, ion toxicity, and nutrient imbalances. Salinity also reduces chlorophyll content, leading to lower leaf greenness and photosynthetic efficiency through impaired stomatal conductance and transpiration. In addition, saline water disrupts ion uptake, increasing Na+ and Cl- accumulation and disrupting the balance of essential nutrients like K+ and Ca2+. These physiological and visual responses are species-specific. Therefore, this review synthesizes current findings on the impact of salinity stress on ornamental plants, with a focus on aesthetic value, growth performance, photosynthetic traits, and ion homeostasis. It aims to inform sustainable irrigation practices and species selection for nursery production and landscape applications using alternative water sources with salinity concerns.